Old rivalries, new arsenals should the US worry?. - Zakheim, D.S (IEEE spectrum)
Could a small country develop the capability to hit the United States with a long-range unconventional weapon during the first decades of the next century? Most certainly one could. But whether such a state would be inclined to try is an entirely different matter. The risk is real. Congress learned in 1998, according to ?The Report of The Commission to Assess the Ballistic Missile Threat to the United States?, that the United States has entered ?a new nonproliferation environment? in which there is a far greater availability of ballistic missiles and weapons of mass destruction. The main points of the report are discussed and a table is given showing the ballistic missile types held by lesser powers